Socio-psychological factors associated with the public's willingness to pay for elite sport policy: does risk perception matter? - Funahashi, H.; Mano, Y. (Managing Sport and Leisure, 2014)
We present the results of an application of the contingent valuation method to an elite sport policy. Specifically, we aimed to address the literature gap by introducing risk perception as one of the socio-psychological factors explaining the willingness to pay (WTP) for the elite sport policy which is based on an attitudinal framework. The respondents were asked about their WTP for the Japanese elite sport policy. The annual median and truncated mean WTP were estimated at 513 and 1802 JPY (€4.15 and €14.59), respectively, through a log logit model. The statistical analysis of WTP determinants indicated that the value of an elite sport policy is based not only on the perceived positive aspects of the outcome of the policy (benefit perception), but also on the negative aspects associated with elite sport development (risk perception). Moreover, viewing athletes as role models was found to be a value driver.